Maternal factors influencing low birth weight babies - Prudhivi, Srinivas; Bhosgi, Revanasiddappa (International Journal of Contemporary Pediatrics, 2017)
Background: This study was conducted to know the maternal and biosocial factors that influence low birth weight babies. Maternal education, occupation, Parity, Malnutrition and anaemia did have a significant impact on birth weight. Methods: This was a prospective study involving babies born at Dr.PSIMS & RF, Chinaoutapalli conducted over a period of 2.5 years from June 2009 to October 2011. There were a total of 450 babies in this study, of which 150 were low birth weight babies and the rest 300 babies were weighing 2.5 kg or more. To ascertain the maternal factors responsible for low birth weight babies, study of which will enable us to understand the measures involved in reducing the neonatal mortality and morbidity. Results: In this study, an analysis 150 mothers of LBW babies was done and compared with 300 normal weight babies. The variables were subjected to computer analysis using focus format. The data was analysed using a Chi-Square for quantitative data. Chi square test was used to calculate p value. P value was considered significant if <0.05. SPSS version 16 software is used to do the necessary statistical calculations. Conclusions: In mothers who had no education & Mothers belonging to lower socioeconomic class had higher chance of delivering low birth weight babies. Parity has a significant relationship with birth weight. There is significant association of PIH and oligohydramnious with birth weight. Maternal malnutrition and anaemia have a significant association with LBW.